Factors Influencing the Information Support Provided by Health Care Professionals to Patients in a Dialysis Center Regarding Kidney Transplantation: A Nationwide Study - Paulina Kurleto; Lucyna Tomaszek; Irena Milaniak; Grażyna Dębska; Edyta Turkanik; Barbara Siekierska; Roman Danielewicz; Alicja Dębska-Ślizień (Transplant International)
For patients undergoing renal replacement therapy, kidney transplantation (KTx) is the preferred therapeutic method. The aim of this study was to investigate selected factors affecting the information support provided by healthcare professional to patients in dialysis center regarding KTx. A multiple logistic regression was carried out to assess the relationship between information support, socio-demographic factors, life satisfaction (Satisfaction with Life Scale), self-esteem (Self-Esteem Scale), perceived self-efficacy (General Self-Efficacy), attitude, knowledge about organ transplantation. Of the 1,093 respondents aged 22–72 years, 501 respondents (45.8%) always informed patients about the possibility of treatment with KTx. Physicians vs. nurses (OR = 1.79; Cl 95%: 1.48–2.16), and those who supported legalization of unspecified living kidney donation in Poland (OR = 1.30; Cl 95%: 1.07–1.59) and believed that blood donation is safe (OR = 1.29; Cl 95%: 1.12–1.47) were more likely to provide informational support. Knowledge level (OR = 1.32; Cl 95%: 1.18–1.47) and self-esteem (OR = 1.06; Cl95%: 1.03–1.10) correlated positively with information support. Male participants were less likely to provide informational support than females (OR = 0.78; Cl 95%: 0.62–0.99). The results reveal inadequate information provided by healthcare professional to patients about KTx. This highlights the urgent need for comprehensive educational programs.